Exploring Magnetic Anisotropy and Exchange Coupling in feiii2dyiii Heterotrimetallic Assemblies Displaying Slow Relaxation of Magnetization - Aravena-Ponce, D; Aravena-Ponce, D (ROYAL SOC CHEMISTRY, 2025)
Three new FeIII2DyIII heterotrinuclear complexes were synthesized using structurally related, yet distinct, Schiff base ligands in combination with acetate, phenoxide, or methoxide bridging groups. X-Ray crystallographic analyses reveal that, despite variations in the ligand backbones and donor atoms, all complexes share a common Fe2Dy core, exhibiting only subtle differences in the Fe-O-Dy angles and in the coordination environment around the DyIII center. Direct-current (DC) magnetic measurements establish high-spin FeIII ions (S = 5/2) and an overall ferromagnetic Fe-Dy exchange, while alternating-current (AC) data show clear out-of-phase signals under zero DC field, consistent with single-molecule magnet (SMM) behavior. The effective energy barriers for magnetization reversal (Ueff = 17-26 K) depend on the nature of the bridging ligand and the coordination environment around DyIII ion. Ab initio CASSCF and broken-symmetry DFT calculations support the experimental observations, demonstrating that axial DyIII anisotropy is preserved while the strength of the Fe-Dy coupling subtly adjusts the relaxation dynamics. These results highlight that the minor structural variations at the bridging ligands markedly influence the balance between exchange interactions and crystal-field effects, thereby advancing the understanding of Fe-Ln based SMMs.